Seroprevalence of Toxoplasmosis among Human Immunodeficiency Virus infected pregnant women in Abuja Teaching Hospital, Nigeria - Zakari, Maryam Muhammad; Isah, Aliyu Yabagi; Offiong, Richards; Yunusa, Thairu; Abdullahi, Idris Nasir (European Journal of Clinical and Experimental Medicine, 2020)
<p class="rtejustify" style="box-sizing: border-box; margin: 0px 0px 1em; line-height: 20px; color: #010101; font-size: 14px; text-align: justify; font-family: Lato, sans-serif; font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 400; letter-spacing: 0.1px; orphans: 2; text-indent: 0px; text-transform: none; widows: 2; word-spacing: 0px; -webkit-text-stroke-width: 0px; white-space: normal; background-color: #ffffff; text-decoration-thickness: initial; text-decoration-style: initial; text-decoration-color: initial;">Introduction. Toxoplasmosis is a neglected parasitic infection that has economic and epidemiological significance. Data on toxoplasmosis seroprevalence among Human Immunodeficiency Virus (HIV) infected pregnant women may be of obstetric and neonatal concern. <p class="rtejustify" style="box-sizing: border-box; margin: 0px 0px 1em; line-height: 20px; color: #010101; font-size: 14px; text-align: justify; font-family: Lato, sans-serif; font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 400; letter-spacing: 0.1px; orphans: 2; text-indent: 0px; text-transform: none; widows: 2; word-spacing: 0px; -webkit-text-stroke-width: 0px; white-space: normal; background-color: #ffffff; text-decoration-thickness: initial; text-decoration-style: initial; text-decoration-color: initial;">Aim. The study was designed to determine the seroprevalence of Toxoplasmosis and associated risk factors in HIV-positive pregnant women attending the University of Abuja Teaching Hospital, Abuja, Northcentral Nigeria. <p class="rtejustify" style="box-sizing: border-box; margin: 0px 0px 1em; line-height: 20px; color: #010101; font-size: 14px; text-align: justify; font-family: Lato, sans-serif; font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 400; letter-spacing: 0.1px; orphans: 2; text-indent: 0px; text-transform: none; widows: 2; word-spacing: 0px; -webkit-text-stroke-width: 0px; white-space: normal; background-color: #ffffff; text-decoration-thickness: initial; text-decoration-style: initial; text-decoration-color: initial;">Material and methods. This was a hospital-based cross-sectional study. A total of 160 HIV seropositive pregnant women were recruited. Blood samples were collected and tested for anti-T. gondii IgM and IgG using Enzyme Linked Immunosorbent Assay (ELISA). Structured questionnaires were used to collate the sociodemographic variables of participants. <p class="rtejustify" style="box-sizing: border-box; margin: 0px 0px 1em; line-height: 20px; color: #010101; font-size: 14px; text-align: justify; font-family: Lato, sans-serif; font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 400; letter-spacing: 0.1px; orphans: 2; text-indent: 0px; text-transform: none; widows: 2; word-spacing: 0px; -webkit-text-stroke-width: 0px; white-space: normal; background-color: #ffffff; text-decoration-thickness: initial; text-decoration-style: initial; text-decoration-color: initial;">Results. Out of the 160 of HIV seropositive pregnant women, the seroprevalence anti-T. gondii IgG and IgM were 29.4% and 4.4%, respectively. There was no significant association between anti-T. gondii and all sociodemographic variables studied (p>0.05). <p class="rtejustify" style="box-sizing: border-box; margin: 0px 0px 1em; line-height: 20px; color: #010101; font-size: 14px; text-align: justify; font-family: Lato, sans-serif; font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 400; letter-spacing: 0.1px; orphans: 2; text-indent: 0px; text-transform: none; widows: 2; word-spacing: 0px; -webkit-text-stroke-width: 0px; white-space: normal; background-color: #ffffff; text-decoration-thickness: initial; text-decoration-style: initial; text-decoration-color: initial;">Conclusion. The overall result of this study revealed that the majority of pregnant women were exposed to toxoplasmosis much earlier in life. Hence, these findings will assist obstetricians and gynecologists in the early diagnosis and management of Toxoplasma gondii infection in pregnant women, especially HIV coinfected ones with IgM seropositivity.